Effects of Ramadan on clinical visits at a primary health center in a Rohingya refugee camp in Bangladesh. - Taizo Sakata; Odgerel Chimed-Ochir; Md Omar Sharif Ibne Hasan; Mototaka Inaba; Yasuhiko Kamiya; Yui Yumiya; Tatsuhiko Kubo (PLOS Global Public Health)
In 2017, hundreds of thousands of Rohingya fled Myanmar to refugee camps in Cox's Bazar in southeastern Bangladesh. Peace Winds Japan and Dhaka Community Hospital Trust have jointly operated a primary health center (PHC) at Camp 14 in this region since 2018. Our objective was to determine the effect of Ramadan on clinical visits at this PHC during 2020. We conducted a retrospective analysis of patient data, including diagnoses and use of medications, by review of medical records from January to December 2020. We compared the percentage of visits for five health events (acute respiratory infection [ARI], non-communicable disease [NCD], gastritis, female related issues, and injury) for three consecutive 31-day periods: before Ramadan period (BR-period), Ramadan period, and after Ramadan period (AR-period). There were 11,286 PHC visits during 2020. The rate of new patient visits was significantly lower during Ramadan than during the BR-period (aOR: 0.447; 95%CI: 0.356, 0.561; P < 0.001). The three periods had no significant differences in mean patient age, patient sex, or surgical procedures. The most noteworthy differences were fewer visits for NCD during Ramadan than during the BR-period (OR: 0.461; 95%CI: 0.307, 0.693; P < 0.0004); more visits for gastritis during Ramadan than during the BR-period (OR: 1.246; 95%CI: 1.106,1.404; P = 0.0019); and more visits for ARI during Ramadan than during the AR-period (aOR: 1.842; 95%CI: 1.567, 2.164, P < 0.0001). The overall decrease in PHC visits during Ramadan relative to the BR-period may be because these refugees devoted more time to prayer and associated religious practices during Ramadan, and therefore had less time available for visiting the PHC. The sharp decline in PHC visits for NCD and several other health events during Ramadan relative to the BR-period highlights the need to provide improved care for refugees during this period.